2014
DOI: 10.1017/thg.2014.4
|View full text |Cite
|
Sign up to set email alerts
|

Association Between ERCC2 Lys751Gln Polymorphism and Lung Cancer Risk: A Meta-Analysis Involving 23,370 Subjects

Abstract: Recent studies report a correlation between excision repair cross-complementing group 2 (ERCC2) Lys751Gln polymorphism and an increased risk of lung cancer, but results are controversial and inconclusive. Thus, we conducted a comprehensive meta-analysis in order to assess the correlation between them. Our study uses an odds ratio (OR) with a 95% confidence interval (95% CI) to evaluate the strength of the association; we also performed Begg's funnel plot and the Egger's test to assess the publication bias of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Moreover, so many meta-analysis had investigated the association between the gene polymorphisms and the risk of lung cancer. The meta-analysis of Tan et al [ 25 ] had reported a correlation between (ERCC2) Lys751Gln polymorphism and an increased risk of lung cancer based on 23,370 subjects. Wang et al [ 26 ] performed a meta-analysis showed that there was no association between IL-6 rs1800796 polymorphism and lung cancer, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, so many meta-analysis had investigated the association between the gene polymorphisms and the risk of lung cancer. The meta-analysis of Tan et al [ 25 ] had reported a correlation between (ERCC2) Lys751Gln polymorphism and an increased risk of lung cancer based on 23,370 subjects. Wang et al [ 26 ] performed a meta-analysis showed that there was no association between IL-6 rs1800796 polymorphism and lung cancer, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneity across studies was tested by a chi-square-based Q test (heterogeneity was considered to exist between studies when p < .10 and I 2 > 25% for the Q test, with 25% < I 2 < 50% regarded as low heterogeneity, 50% ≤ I 2 ≤ 75% regarded as moderate heterogeneity, and I 2 > 75% as high heterogeneity). We calculated pooled ORs with a fixed-effects model if there was no heterogeneity; where the p value was <.10, a random-effect model was adopted (Tan et al, 2014). If heterogeneity was observed, meta-regression analyses would be performed to explore the potential source of the heterogeneity (Higgins & Thompson 2004; Thompson & Higgins, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Many epidemiological studies with the aim of identifying the role of ERCC2 polymorphisms in the risk of various cancers have been done and different association between Lys751Gln polymorphism and the risk of lung cancer [ 3 5 ], glioma [ 6 ], colorectal cancer [ 7 ], breast cancer [ 8 , 9 ], and esophageal squamous cell carcinoma [ 10 ] has been reported.…”
Section: Introductionmentioning
confidence: 99%